Self-made spoon-shaped tool for removal of magnetic foreign bodies from the bladder: a case report - Zhang, Zhi Yuan; Deng, Huan; Liang, Qi Chun; Wang, Yi He (Frontiers in Surgery, 2025)
BackgroundForeign bodies retained in the urethra or bladder present a rare but complex challenge in adult urological practice. Magnetic beads, in particular, are difficult to manage due to their mutual attraction and the large quantities often involved. The presence of such beads complicates removal procedures, especially in male patients with a long urethra. We describe a novel and simple method for retrieving magnetic beads from the bladder.Case descriptionA 23-year-old man presented with painful urination after inserting approximately 40 small magnetic beads into his urethra for sexual stimulation. Pelvic computed tomography confirmed the presence of multiple metallic bodies in the bladder. Given his preference for a minimally invasive approach and opposition to open surgery, we devised a novel retrieval method. To remove the foreign bodies in a minimally invasive manner, we used orthopedic wire to create a spoon-shaped extractor, which was inserted through a resectoscopic sheath. Using direct cystoscopic visualization, the extractor successfully removed up to six beads at a time. A total of 48 beads were retrieved from the bladder, and the patient was discharged on the second postoperative day, with no complications or residual symptoms.ConclusionsThe self-made extractor reduced the risks associated with removing spherical foreign bodies and shortened the overall surgical time. This new device offers valuable insights into the efficient removal of spherical objects from the bladder, making it suitable for primary care settings where conventional instruments may be limited.